Methodological approaches and rationale for training to prevent anterior cruciate ligament injuries in female athletes - Myer, G. D.; Ford, K. R.; Hewett, T. E. (Scandinavian Journal of Medicine & Science in Sports, 2004)
Female athletes have a four- to sevenfold increased risk of anterior cruciate ligament (ACL) injury compared with their male counterparts playing at similar levels in the same sports. The elevated risk of ACL injury in females coupled with the geometric increase in female sports participation in the last 30 years has led to a rapid rise in these injuries. This large increase in ACL injury incidence has fueled studies into both mechanisms of injury and interventions to prevent injury. A review of published multidisciplinary approaches demonstrates that several training protocols have utilized multiple components targeted toward injury prevention training and were able to reduce injury incidence in female athletes. Similar training techniques may also be used to gain improvements in measures of performance. The purpose of this review is to highlight training components that may reduce ACL injury risk and assess their potential for combined use in performance-oriented protocols.